2014
DOI: 10.1186/1471-2474-15-191
|View full text |Cite
|
Sign up to set email alerts
|

Synaptosomal-associated protein 25 (Snap-25) gene Polymorphism frequency in fibromyalgia syndrome and relationship with clinical symptoms

Abstract: BackgroundSNAP-25 protein is contributory to plasma membrane and synaptic vesicle fusions that are critical points in neurotransmission. SNAP-25 gene is associated with behavioral symptoms, personality and psychological disorders. In addition, SNAP-25 protein can be related to different neurotransmitter functions due to its association with vesicle membrane transition and fusion. This is important because neurologic, cognitive, and psychologic disorders in fibromyalgia syndrome (FMS) can be related to this fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
(27 reference statements)
1
6
0
1
Order By: Relevance
“…For this reason, SNAP-25 may be contributing to the pathogenesis of FMS by mediating the release of neurotransmitters such as serotonin and dopamine. In a study carried out by Balkarli et al 11 which was the preliminary of our study, it was reported that SNAP-25 gene polymorphism was more frequently detected in FMS. Depression and pain score was higher in patients with DdeI T/C genotype.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…For this reason, SNAP-25 may be contributing to the pathogenesis of FMS by mediating the release of neurotransmitters such as serotonin and dopamine. In a study carried out by Balkarli et al 11 which was the preliminary of our study, it was reported that SNAP-25 gene polymorphism was more frequently detected in FMS. Depression and pain score was higher in patients with DdeI T/C genotype.…”
Section: Introductionsupporting
confidence: 53%
“…In a study of Balkarli et al 11 , it was found that SNAP-25 gene polymorphism was more frequently detected in FMS. Depression and pain score was higher in patients with DdeI T/C genotype.…”
Section: Discussionmentioning
confidence: 96%
“…SNAP-25 protein is a SNARE protein, critical in neurotransmitter release (51). Aberrancies in this protein are described in several neurological, cognitive and psychological disorders like Alzheimer's disease and fibromyalgia (5255). Also UCHL1 is particularly abundant in the brain, where it is critical for proper function of the ubiquitin-proteasome system in neurons (56).…”
Section: Discussionmentioning
confidence: 99%
“…While the pathways with increased gene products include glucocorticoid signaling and B-cell development, there has been no obvious pathologic dysfunction of these pathways noted in FMS. Rather than being an immunologic failing, the atypical B-cell findings appear to be another aspect of the organism-wide alterations in physiology noted in FMS, such as the reported alterations in pain processing, autonomic and neuroendocrine function, neurotransmitter concentrations, and small-fiber nerve density (Balkarli, Sengul, Tepeli, Balkarli, & Cobankara, 2014; Oaklander, Herzog, Downs, & Klein, 2013; Serra et al, 2014). Understanding the significance of these B-cell differences requires knowing whether such differences precede and predispose people to future symptom development, are causal in creating symptoms, or are just an epiphenomenon that accompanies or instantiates the experience of symptoms.…”
Section: Discussionmentioning
confidence: 99%